Aboriginal talking circle: Aboriginal perspectives on caribou conservation - Overview by the Aboriginal Talking Circle Coordinating Team - Simmons, Deborah; Bayha, Walter; Beaulieu, Danny; Gladu, Daniel; Manseau, Micheline (Rangifer, 2012)
The 13th North American Caribou Workshop in 2010 was the venue for a remarkable forum of Aboriginal knowledge holders in which experiences and ideas about caribou research and stewardship were shared in a Talking Circle format. Facilitated by Danny Beaulieu (Denesųłıné /Deninu Kųę First Nation) and Walter Bayha (Dé lįnęgotı˛nę/Dé lı˛nę First Nation), the Aboriginal Talking Circle took place over a full day as well as a half day, totalling more than ten hours. At least thirty-six Aboriginal people contributed to the discussion, representing thirty organisations and nearly as many First Nation, Inuit and Métis nations. Delegates converged from a geographical area spanning caribou ranges in six provinces and all three territories of northern Canada.